EFEKTIVITAS PEMBELAJARAN SERVIS BAWAH PERMAINAN BOLAVOLI BERBASIS MULTIMEDIA DI SMA YP YAQLI OKU TIMUR SUMATERA SELATAN - Muhsana Elcintami Lanos; Hikmah Lestari (Riyadhoh : Jurnal Pendidikan Olahraga, 2022)
This research uses quantitative methods. This study aims to determine the effectiveness of implementing multimedia-based volleyball game underhand learning in class X High School (SMA). The research design in this study was one control group pretest-posttest. The research was conducted at SMA YP Yaqli OKU Timur, South Sumatra. Based on the results of the test of the effectiveness of the application of multimedia-based volleyball underhand learning in class X High School (SMA) that has been carried out, the results of the N-Gain Score test on the learning outcomes of volleyball underhand serve obtained an average N-Gain Score for the class experiment of 93.5% in the "effective" category, the minimum N-Gain Score is 81.8% and the maximum N-Gain Score is 100%. While the average N-Gain Score for the control class is 31.3% in the "ineffective" category, the minimum N-Gain Score is 19.2% and the maximum N-Gain Score is 52.3%, so that it can be concluded that the application of service learning development Multimedia-based volleyball has proven to be effective so that it can improve the underhand serve skills of class X SMA YP Yaqli OKU East, South Sumatra. So from the results of this study it is suggested to teachers, coaches and novice athletes to be able to use the multimedia-based under serve learning product that has been developed.